1993
DOI: 10.1111/j.1365-2958.1993.tb01654.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ferric enterobactin receptor (PfeA) of Pseudomonas aeruginosa: involvement of a two‐component regulatory system

Abstract: Expression of the ferric enterobactin receptor in Pseudomonas aeruginosa is inducible by enterobactin and requires sequences upstream of the structural gene (pfeA). Nucleotide sequencing of a 2.5 kilobase pair (kb) region of DNA immediately upstream of pfeA revealed two open reading frames (ORFs), pfeR and pfeS, which appeared to comprise an operon. The predicted products of pfeR and pfeS (molecular weight 26,796 and 50,597, respectively) exhibited a high degree of homology to response-regulator and sensor com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
113
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 42 publications
1
113
0
Order By: Relevance
“…This inner-membrane-spanning protein then activates two ECFsigma factors, PvdS and FpvI, which are required for the transcription of pyoverdine biosynthesis and uptake genes, respectively (Beare et al, 2003;Lamont et al, 2002;Redly & Poole, 2003). Perception of the heterologous Escherichia coli siderophore enterobactin occurs in the periplasm by the sensor kinase PfeS, which activates its cognate response regulator PfeR by phosphorylation such that PfeR becomes able to upregulate the transcription of the outer-membrane receptor gene pfeA (Dean & Poole, 1993;Dean et al, 1996). Pyochelin sensing occurs in the cytoplasm of P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…This inner-membrane-spanning protein then activates two ECFsigma factors, PvdS and FpvI, which are required for the transcription of pyoverdine biosynthesis and uptake genes, respectively (Beare et al, 2003;Lamont et al, 2002;Redly & Poole, 2003). Perception of the heterologous Escherichia coli siderophore enterobactin occurs in the periplasm by the sensor kinase PfeS, which activates its cognate response regulator PfeR by phosphorylation such that PfeR becomes able to upregulate the transcription of the outer-membrane receptor gene pfeA (Dean & Poole, 1993;Dean et al, 1996). Pyochelin sensing occurs in the cytoplasm of P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…Additional transcriptional regulators have been identified that can act as positive regulators of siderophore biosynthesis and transport gene expression, all of which are Fur controlled and responsive to the presence of the cognate iron chelate (14,18,23,24,28). The concerted actions of negatively and positively acting regulators in bacterial species capable of utilizing diverse iron sources may ensure that genes encoding specific nutritional iron transport functions are expressed maximally only under appropriate conditions in which the particular iron source is perceived in the environment, thus conserving energy and precursors.…”
mentioning
confidence: 99%
“…In the present work, PvdI and FpvAI are called Pvd and FpvA, respectively. FpvA has been well characterized using physiological, immunological, and molecular approaches (see references 11,16,50, and 51, among others). The structures of P. aeruginosa FptA and FpvA have been solved (12,13).…”
mentioning
confidence: 99%